2021
DOI: 10.1183/16000617.0103-2021
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus-related lung disease in people with cystic fibrosis: can imaging help us to diagnose disease?

Abstract: In people with cystic fibrosis (PwCF), viscous sputum and dysfunction of the mucociliary escalator leads to early and chronic infections. The prevalence of Aspergillus fumigatus in sputum is high in PwCF and the contribution of A. fumigatus to the progression of structural lung disease has been reported. However, overall, relatively little is known about the contribution of A. fumigatus to CF lung disease. More knowledge is needed to aid clinical decisions on whether to start antifungal treatment. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 129 publications
0
7
0
Order By: Relevance
“…These coinfected pathogens might release cytotoxic substances that cause damages to the epithelium, favoring the colonization and germination of A. fumigatus. The medicine used for other co-infected pathogens might also counteract antifungal medicine (Lv et al, 2021). In this study, we found that A. fumigatus could stimulate G-CSF production, which contributed to the activation of neutrophils with lower apoptosis rate (Figures 6A,B and Supplementary Figures 1B,C), which implies a pleiotropic role of G-CSF and neutrophils during infections.…”
Section: Discussionmentioning
confidence: 56%
“…These coinfected pathogens might release cytotoxic substances that cause damages to the epithelium, favoring the colonization and germination of A. fumigatus. The medicine used for other co-infected pathogens might also counteract antifungal medicine (Lv et al, 2021). In this study, we found that A. fumigatus could stimulate G-CSF production, which contributed to the activation of neutrophils with lower apoptosis rate (Figures 6A,B and Supplementary Figures 1B,C), which implies a pleiotropic role of G-CSF and neutrophils during infections.…”
Section: Discussionmentioning
confidence: 56%
“…The lack of evaluating chest imaging is also a limitation of our study because it has been shown that Aspergillus spp. is associated with structural lung disease 15,39,40 . On the other hand, the strength of our study is its prospective longitudinal design.…”
Section: Discussionmentioning
confidence: 95%
“…is associated with structural lung disease. 15,39,40 On the other hand, the strength of our study is its prospective longitudinal design.…”
Section: In Conclusion Althoughmentioning
confidence: 99%
“…[6] Patients with pre-existing conditions such as asthma or cystic fibrosis are more likely to develop allergic forms of aspergillosis. [7] The chronic forms of aspergillosis are associated with long-term cough or other pulmonary and systemic symptoms. It is most commonly observed in patients with lung damage but with no significant immunocompromise.…”
Section: Introductionmentioning
confidence: 99%